FACTORS RELATED TO BULLYING IN JUNIOR HIGH SCHOOL STUDENTS IN PADANG CITY - Nurliza, Okta; Ramadani, Mery; Yuni, Hamidatul (Universitas Muhammadiyah Ponorogo, 2025)
Bullying can occur at all educational levels and in social settings, with 75.9% of adolescents having experienced it. This study aims to identify factors related to bullying behavior among students at SMPN 24 and SMP Muhammadiyah 5 in Padang City in 2025. Using a quantitative cross-sectional design, 266 students were sampled from a population of 790 through proportionate random sampling. Data were collected via questionnaires and analyzed using the chi-square test from October 2024 to April 2025. Results showed that 54.1% of students had a high level of bullying behavior. Contributing factors included negative attitudes (p=0.000), poor school environment (p=0.000), low peer support (p=0.020), and strong influence of social media (p=0.000). As bullying levels are high, it is recommended that schools implement monthly education programs addressing the causes, impacts, and prevention of bullying to raise awareness among students and teachers and discourage the normalization of such behavior